The specificity of law enforcement in competitive swimming from the perspective of Indonesia’s national legal system - Ismanto, Barru Aliyyu Nissa (Privietlab, 2026)
This article discusses the specificity of law enforcement in swimming from the perspective of Indonesia's national legal system. This study focuses on the applicability of international sports organization regulations as normative standards in the implementation of competitive sports, particularly based on Law No. 11 of 2022 on Sports. This study uses a normative legal research method with regulatory and conceptual approaches to the problem. The results of the study show that the enforcement of swimming law has specific characteristics that originate from lex sportiva, a private normative system that is recognized to a limited extent by national laws. The application of the core regulations of international sports organizations is a legal requirement for recognizing an activity as competitive. If these regulations are not applied in their entirety and consistently, championships or sports weeks cannot be classified as competitive sports within the framework of the national law. This study confirms that the recognition of lex sportiva is conditional and remains within the limits of the constitutional principles and the protection of human rights.